Evaluation of changes in the faecal resistome associated with children's exposure to domestic animals and food animal production. (December 2022) - Cifuentes, Sara G.; Graham, Jay; Loayza, Fernanda; Saraiva, Carlos; Salinas, Liseth; Trueba, Gabriel; Cárdenas, Paúl A.
Highlights: The paediatric gut microbiota is a reservoir of antimicrobial resistance genes. The abundance of specific antimicrobial resistance genes is significantly different between risk groups. Animal exposure did not affect the overall paediatric gut resistome structure. ABSTRACT: Objectives: The paediatric gut microbiota is a reservoir of antimicrobial resistance genes. Environmental factors such as a child's exposure to faecal contamination and antimicrobial resistance genes of animal origin likely shape the resistome of infants and children. This study measured how different levels of exposure to domestic or food animals affect the structure of the intestinal resistome in children between 1 and 7 years of age. Methods: One hundred nineteen faecal samples from 39 children were analysed according to the level of exposure to domestic or food animals and categorized into three risk groups. Using high-throughput sequencing with an Illumina NovaSeq 6000 SP platform, we performed faecal resistome analyses using the ResFinder database. Additionally, ResistoXplorer was used to characterize the resistomes of children differentially exposed to domestic animals. Results: Our data indicated that specific antimicrobial resistance genes such as those that confer resistance to MATFPR (macrolide, aminoglycoside, tetracycline, fluoroquinolone, phenicol, and rifamycin) and tetracyclines were statistically less abundant in the group of children without exposure to animals (group 2), compared with the groups exposed to domestic and food animals (groups 1 and 3). However, the overall resistome structure among the children was not affected by the different levels of exposure to animals. Conclusions: This study suggests that animal exposure is a risk factor for young children acquiring specific antimicrobial resistance genes from domestic animals or animal production areas. However, the overall resistome structure was not affected. Graphical abstract: Image, graphical abstract